2019
DOI: 10.1016/j.biopsycho.2019.107746
|View full text |Cite
|
Sign up to set email alerts
|

Using event-related potential and behavioural evidence to understand interpretation bias in relation to worry

Abstract: Wo rry is a common experience, thought to be maintained by the tendency of interpreting ambiguous information in a consistent (e.g. negative) manner, termed "interpretation bias". This study explored whether high worriers (Penn State Worry Questionnaire score, PSWQ ≧ 56) and low worriers (PSWQ score ≦ 39) show different interpretation biases, and examined at which stages of information processing these interpretation biases occur. Participants with high and low worry levels completed interpretation assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…In line with previous research on socially anxious populations using the LDT to examine interpretation bias (Hirsch & Mathews, 1997;2000), Feng et al (2019) reported that low worriers displayed a positive interpretation bias, whereas high worriers demonstrated neither a positive nor negative bias, evidenced by both reaction time and N400 ERP interpretation bias indices. In contrast to the N400 findings in Feng et al (2019), the earlier of Moser's studies (Moser, Hajcak, Huppert, Foa, & Simons, 2008) failed to find an N400 difference between high and low socially anxious groups in an interpretation assessment task, where ambiguous sentences were resolved in a negative or positive manner by the final grammatically correct words. Unlike Feng et al (2019) or the current study, Moser et al (2008) also looked at P600, a later ERP that has the potential to indicate whether expected interpretations are violated or not (i.e., expectation violation effect).…”
Section: Online and Offline Markers Of Interpretation Biassupporting
confidence: 86%
See 3 more Smart Citations
“…In line with previous research on socially anxious populations using the LDT to examine interpretation bias (Hirsch & Mathews, 1997;2000), Feng et al (2019) reported that low worriers displayed a positive interpretation bias, whereas high worriers demonstrated neither a positive nor negative bias, evidenced by both reaction time and N400 ERP interpretation bias indices. In contrast to the N400 findings in Feng et al (2019), the earlier of Moser's studies (Moser, Hajcak, Huppert, Foa, & Simons, 2008) failed to find an N400 difference between high and low socially anxious groups in an interpretation assessment task, where ambiguous sentences were resolved in a negative or positive manner by the final grammatically correct words. Unlike Feng et al (2019) or the current study, Moser et al (2008) also looked at P600, a later ERP that has the potential to indicate whether expected interpretations are violated or not (i.e., expectation violation effect).…”
Section: Online and Offline Markers Of Interpretation Biassupporting
confidence: 86%
“…In contrast to the N400 findings in Feng et al (2019), the earlier of Moser's studies (Moser, Hajcak, Huppert, Foa, & Simons, 2008) failed to find an N400 difference between high and low socially anxious groups in an interpretation assessment task, where ambiguous sentences were resolved in a negative or positive manner by the final grammatically correct words. Unlike Feng et al (2019) or the current study, Moser et al (2008) also looked at P600, a later ERP that has the potential to indicate whether expected interpretations are violated or not (i.e., expectation violation effect). They found a difference in interpretation bias, indicated by P600, between high and low socially anxious groups.…”
Section: Online and Offline Markers Of Interpretation Biasmentioning
confidence: 56%
See 2 more Smart Citations
“…In this first study of interpretation training in pregnant worriers, we successfully induced a positive interpretation bias using CBM-I. Consistent with Hirsch et al (2009) and Feng et al (2019), participants in the CBM-I condition reported fewer negative thought 3) As GAD7 scores were significantly different at baseline we re-ran the regression analysis with mean centred GAD7 scores and an interaction variable of (mean centred) GAD7 and condition. Neither GAD7 scores (p = .67) or the interaction term (p = .54) were significant predictors in the model.…”
Section: Discussionmentioning
confidence: 99%